Eosinophilic Meningitis Secondary to Intravenous Vancomycin. (June 2013) - Kazi, Ruchika; Kazi, Haseeb A.; Ruggeri, Cara; Ender, Peter T.
Eosinophilic meningitis may be due to infectious or noninfectious etiologies. Parasitic infections cause this entity most frequently and of the noninfectious causes, medications play an important role. We describe a 32-year-old male who developed eosinophilic meningitis while receiving intravenous vancomycin. No other apparent cause of the eosinophilic meningitis was appreciated. This case represents the first description of eosinophilic meningitis due to systemic vancomycin.